2000
DOI: 10.1128/jb.182.16.4466-4477.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Serotype of Type Ia and III Group B Streptococci Is Determined by the Polymerase Gene within the Polycistronic Capsule Operon

Abstract: Streptococcus agalactiae is a primary cause of neonatal morbidity and mortality. Essential to the virulence of this pathogen is the production of a type-specific capsular polysaccharide (CPS) that enables the bacteria to evade host immune defenses. The identification, cloning, sequencing, and functional characterization of seven genes involved in type III capsule production have been previously reported. Here, we describe the cloning and sequencing of nine additional adjacent genes, cps III FGHIJKL, neu III B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 62 publications
7
94
0
Order By: Relevance
“…The above results are in agreement with previous data from Chaffin et al (36), who reported that a single gene can confer GBS serotype specificity. In that case, the authors reported that cpsH differences were solely responsible for the structural diversity between types Ia and III.…”
Section: Discussionsupporting
confidence: 83%
“…The above results are in agreement with previous data from Chaffin et al (36), who reported that a single gene can confer GBS serotype specificity. In that case, the authors reported that cpsH differences were solely responsible for the structural diversity between types Ia and III.…”
Section: Discussionsupporting
confidence: 83%
“…Selection for double recombination events using kanamycin or chloramphenicol selection and screening for loss of plasmid replication (erythromycin sensitivity) was carried out as described previously (39). At least four independent colonies were obtained from A909/pLR5 that were stk1 mutants (Stk1 Ϫ ).…”
Section: Methodsmentioning
confidence: 99%
“…A909 (WT) is a type Ia capsular polysaccharide clinical isolate of GBS (38). Recombinant DNA and other techniques were performed as described (39). Open reading frame (ORF) and BLAST homology searches were performed using the NCBI Internet server (www.ncbi.nlm.nih.gov).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic basis of Sia biosynthesis in GBS has been localized to a cluster of genes at the transcriptional end of the 16-gene capsule operon (32). Similar to E. coli (33,34), GBS gene products of neuC, neuB, and neuA, respectively, catalyze the epimerization of UDP-GlcNAc to N-acetyl mannosamine (ManNAc) (35), the condensation of ManNAc and phosphoenolpyruvate to form Neu5Ac (36), and the activation of Neu5Ac with CTP, to generate CMP-Neu5Ac (37).…”
Section: Gbs Sia O-acetylationmentioning
confidence: 99%